Mathematical model of the process of mixing semi-liquid feeds in a device with a propeller - M. А. Lushnov (Аграрная наука Евро-Северо-Востока, 2024)
The article considers the issues of using a propeller apparatus for mixing semi-liquid feed mixtures in a mixer with an eccentrically positioned working body in the form of a propeller (screw). Until now, when studying the mixing process, little attention has been paid to the transporting ability of the working body in the form of a propeller agitator. When preparing wet mixtures, agitators with a vertically positioned shaft, which is located in the center of a vertical cylindrical tank, are widely used. When installing the working body horizontally, the propeller having a pumping effect (axial movement), can be used not only for mixing, but also for unloading the finished feed mixture, as well as moving it through pipes over short distances. The existing models of the mixing process do not take into account its stochastic nature. Methods of mathematical description of mixing processes considering the prevailing axial movement of the flow are scarcely developed. The proposed mathematical models make it possible to determine the mixer's performance and the required mixing power. The research was aimed at increasing the effectiveness of preparing a feed mixture in a horizontal mixer of propeller type with an eccentrically positioned working body (screw) and saving energy costs along with raising the productivity. The object of the study was a mixing chamber with eccentrically located working bodies of various diameters (0.2, 0.25 and 0.35 m). During the experiments, the productivity required to drive the motor shaft was determined. It has been experimentally established that increasing the agitator rotation speed from 200 to 400 min-1 with a propeller diameter from 0.2 to 0.35 m and a feed mixture humidity of 84 % leads to an increase in power consumption to 3.5 kW and mixer productivity to 12 m3/h, and the degree of uniformity of feed mixtures is up to 98 %.